Linguistic activism in the translation from Spanish to Quechua: An analysis of the Letras TV Willakun - Lovón Cueva, Marco Antonio (2021)
As of the publication of the Law on Indigenous Languages (Law 29735), the use of native languages in any public and private space has become more relevant in Peru. The proof of this are television projects that include languages other than Spanish; even the creators of this content demonstrate a position in favor of the diffusion of the native languages and their culture. The objective of this article is to analyze the translation work performed by the interpreters of the micronoticist Letras TV Willakun to evaluate it as a case of language activism in favor of theQuechua language and culture. The work concludes that, after interviewing the interpreters and part of the program’s audience, this is a case of important developing activism in the university environment, despite its difficulties in the translation process.